PENGARUH TREN FASHION, GAYA HIDUP, LITERASI SYARIAH, TERHADAP PERILAKU KONSUMTIF MAHASISWA DI UNISNU JEPARA - Khafidhoh, Ayuk Nurul; Susilo, Edi (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2025)
This study aims to identify the influence of sharia literacy, lifestyle, and fashion trends on the consumer behavior of UNISNU Jepara students. This study collected quantitative data using a questionnaire. This study involved active students from various study programs at UNISNU Jepara. Hypothesis testing, t-test, coefficient of determination, and multiple linear regression analysis were applied. The findings of the study indicate that fashion trends and lifestyle have a significant impact both simultaneously and separately on the consumer behavior of UNISNU Jepara students. Lifestyle has a more significant influence than sharia literacy on student consumption behavior.